The Influence of EDTA, Trisodiumcitrate and Heparin on the Ultrastructure of Blood Platelets - Libánská, J (Thrombosis and Haemostasis, 1966)
The differences found in the hyalomere of normal human thrombocytes were: the disperse, fine granular arrangement of the hyalomere in the presence of EDTA, fine netlike appearance in the presence of trisodiumcitrate and the fibrillary arrangement of the hyalomere in thrombocytes of heparinised blood.Differences were also found in the appearance of the granulomere in the presence of heparin, trisodiumcitrate or EDTA. They are evaluated as a result of probable contraction of the granulomere in specimens with heparin.Because of the ability of thrombocytes from heparinised blood to contract, we explain the present results as a picture of isolated retraction of blood platelets, without degranulation occuring during viscous metamorphosis.